Pengembangan Utility Pencetakan Daftar Hadir Kuliah Pada Sistem Matahari Universitas Lampung - Anie Rose Irawati; Dwi Sakethi; Hanna Pratiwi (Universitas Lampung, 2015)
This research developed utility for present list printing on Sistem Matahari which is integrated with Lampung University’s Sistem Informasi Akademik (SIAKAD). Development is done by carrying out an analysis the curent present list. The utility’s development system aims to support user to print the present list for each course in accordance with completeness and better structure. The development used file function with pdf cpdf.dll library extension in PHP programing language and Oracle database. This new utility sistem for present list printing on Sistem Matahari has been applied to the Sistem Informasi Akademik (SIAKAD) University of Lampung.